Abnormal Hot Blank of Oxygen-free Copper Sample Holder and Implications for Laser 40Ar/39 Ar Dating - Wenbei SHI; Zhiyu HAN; Liekun YANG; Fei WANG (Yankuang ceshi)
BACKGROUNDOxygen-free copper (OFC) tray is usually used as a container for samples of laser 40Ar/39Ar dating. The blank of the mass spectrometry system needs to be subtracted from the sample signal before age calculation. The tray’s hot blank of argon, including its amount and isotope ratio will affect the 40Ar/39Ar age calculation. However, the material and structure of the laser window make the laser chamber susceptible to temperatures higher than 150°C during the degassing procedure of laser 40Ar/39Ar dating[4,10]. This temperature may be too low to degas the OFC tray completely during the experiment. Besides, the wells loading the mineral samples limit the direct acquisition of the hot blank of the system. These two points make it very difficult to accurately deduct the blank signal of laser 40Ar/39Ar dating.OBJECTIVESTo testify to the effectiveness of the traditional degassing procedure on the sample holder and evaluate the effect of hot blank on age calculation of laser 40Ar/39Ar dating.METHODSTo confirm the effectiveness of the degassing procedure, the hot blank of OFC trays, which had been exposed to atmosphere for different time intervals were measured by mass spectrometry, after degassing the laser chamber to 150℃ for four days. Loading the standard mineral YBCs sanidine in the well in OFC trays with different duration in air, the argon isotopes were measured after the same degassing procedure. The change of the proportion of atmospheric argon of YBCs will verify if laser energy heats the OFC tray and mineral sample simultaneously.RESULTSThe temperature of the sample holder increases during laser heating of samples. For standard mineral YBCs sanidine placing in OFC tray C, exposed to the atmosphere for about 14 months, the proportion of atmospheric argon was 34.4% (Table 1). This value decreased to 2.0% when YBCs was placed in tray D and degassed by laser at higher energy. This implies that the tray temperature will increase during sample heating by laser, and a considerable amount of gas will be released if the tray is not completely degassed.　　It was proved that heated to about 150℃ was not enough to completely degas the OFC tray during experiment. The hot blank of another two planchettes following the same degassing procedure were measured. For tray A with exposure to the atmosphere for 10 months, the amount of 40Ar released from two wells reached 1.6×10−14−3.1×10−14mol; for tray B with exposure to the atmosphere for 26 months, the 40Ar content increased to 0.8×10−13−2.0×10−13mol. These levels were much higher than the cold background of 3.8×10−16−6.2×10−16mol. Incomplete degassing of the tray may lead to argon isotopic fractionation, resulting in the value of 40Ar/36Ar of the hot blank rise to 310, which is higher than the value of atmospheric argon. Under this condition, using 40Ar/36Ar=295.5[16] or 298.56[17] to correct the atmospheric argon will add extra 40Ar to the sample’s signal and lead to an older age.　　The OFC tray was degassed efficiently while heated with a higher laser power. Under the same degassing procedure, the hot blank of the empty wells in tray D was similar to the cold blank of the system. The OFC trays exposed to air also gave the same conclusion. When the wells in the tray were heated by a lower power energy following a higher power energy, the hot blank dropped to the cold blank level (Fig.2).　　Assuming all of the atmospheric argon contributed from the hot blank with 40Ar/36Ar=310, its effect on 40Ar/39Ar age calculation with different combination of 40Ar*/39ArK, J-value and atmospheric argon content was calculated. Results show that the percent change of age(t%) was mainly controlled by the atmospheric argon content. When the atmospheric argon content increased to 50% (Fig.3), it elevated the age by 5%. Under the same condition, the J-value was about 5.2% lower(Fig.4). In practice, however, the different capacity of adsorption and thermal desorption of gas of different minerals[18-19] makes the effects difficult to quantify.CONCLUSIONSCareful degassing of the OFC tray is needed, especially in very young samples dating through the laser heating method. The temperature of the sample holder increases when the sample is heated by laser, releasing considerable amounts of gas if the holder is incompletely degassed. The limited temperature of the degassing procedure cannot degas the sample holder completely, if the holder adsorbs a lot of gases. There are two possible solutions to solve this problem. The first is pre-degassing the sample holder at 300-400℃ for at least 5 hours at high vacuum furnace after sample exchange. The second is reusing the same sample holder continuously in laser 40Ar/39Ar dating. A combination of both solutions is likely to be most effective.